Change in mode shape nodes of multiple cracked bar: II. The numerical analysis - Khiem, N. T.; Toan, L. K.; Khue, N. T. L. (Vietnam Journal of Mechanics, 2013)
In this paper it is numerically analyzed the change in position of mode shape nodes induced by multiple cracks in bar that has been theoretically investigated in previous paper [1] of the authors. The focus is to analyze thoroughly dislocation of node located intermediately between two cracks in dependence upon the crack parameters without assumption on the smallness of crack.